Data Search System for Thesis and Internship Reports in the Library of the Faculty of Engineering, Gajah Putih University Takengon - Ira Zulfa; Eliyin Eliyin; Rayuwati Rayuwati; Riski Wanda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this research is to develop a data search system for thesis and internship reports at the Faculty of Engineering Library of Gajah Putih University Takengon (UGP). This search engine will be created and used to help students and library employees access thesis and internship report information. Analysis of user needs, system design, creation of effective search algorithms, and evaluation of system performance are all topics that will be discussed in this thesis. Interviews with potential users, satisfaction surveys, and historical data collection of library usage are the methods used. It is expected that the results of this research will help library users find and retrieve thesis and internship report data and improve the accessibility and availability of academic information at the UGP Faculty of Engineering. When search engine technology is used, it is expected that the time required for Information will increase productivity, improve efficiency, and support the academic development of students at UGP.